(untitled) (Altre Modernità, 2010)
The preponderance of death imagery in the mass media and a recent interest of photography in the practice of death suggest the need to reevaluate our approach to death and dying, especially when violence is involved. This essay is a case study of History of Violence, Claudio Cravero’s last photographic project. His collection of "portraits" reproduce apparent dead bodies, mostly attacked in their own domestic spheres, but neither the perpetrator of death (a mysterious murderer?), nor the weapon used (an omnipresent knife), should be considered as main focal points of the artist’s inquiry. The undoubtful protagonist of these photographs, instead, is the light, that illuminates fear: not of death itself, rather of the obnoxious indifference to it, as the result of generalized death imagery saturation. The staged apparent death displayed in Cravero’s photographs serve both as a memento mori and as a strategy to come to terms with the idea of death. In short, it is an apprentship in dying through a domesticating translation practice. Eventually, Cravero’s History of Violence offers a complex reflection on the interplay between each individual story and macrolevel social History, thus providing some hypotheses of where violence and death fit in that odd geometry of time and space that we call life.